2019
DOI: 10.1016/j.geb.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The strategic environment effect in beauty contest games

Abstract: Recent experimental studies have shown that observed outcomes deviate significantly more from the Nash equilibrium when actions are strategic complements than when they are strategic substitutes. This "strategic environment effect" offers promising insights into the aggregate consequences of interactions among heterogeneous boundedly rational agents, but its macroeconomic implications have been questioned because the underlying experiments involve a small number of agents. We studied beauty contest games with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…3 Earlier work has shown that it is much more difficult to coordinate on the unique rational expectations equilibrium under positive than under negative feedback, especially if the system exhibits a near unit root process. For experimental evidence see Heemeijer et al (2009), Sonnemans and Tuinstra (2010) and Hanaki et al (2019). 4 LtFEs are related to repeated number guessing games or beauty contest games, introduced by Nagel (1995).…”
Section: Introductionmentioning
confidence: 99%
“…3 Earlier work has shown that it is much more difficult to coordinate on the unique rational expectations equilibrium under positive than under negative feedback, especially if the system exhibits a near unit root process. For experimental evidence see Heemeijer et al (2009), Sonnemans and Tuinstra (2010) and Hanaki et al (2019). 4 LtFEs are related to repeated number guessing games or beauty contest games, introduced by Nagel (1995).…”
Section: Introductionmentioning
confidence: 99%
“…The role of the strategic environment has been further experimentally investigated in Learning-to-Forecast Experiments (LtFEs, Heemeijer et al 2009, Bao et al 2012, guessing games (Sutan and Willinger 2009, Cooper et al 2017, Hanaki et al 2019 and duopoly games (Potters and Suetens, 2009). 1 The main pattern emerging from these studies is that deviations from equilibrium tend to be larger and more persistent under strategic complementarity as compared to strategic substitutability.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the strategic environment has been further experimentally investigated in Learning-to-Forecast Experiments (LtFEs, Heemeijer et al 2009, Bao et al 2012, guessing games (Sutan and Willinger 2009, Cooper et al 2017, Hanaki et al 2019 and duopoly games (Potters and Suetens, 2009). 1 The main pattern emerging from these studies is that deviations from equilibrium tend to be larger and more persistent under strategic complementarity as compared to strategic substitutability.…”
Section: Introductionmentioning
confidence: 99%
“…SeeHommes (2011) andArifovic and Duffy (2018) for an overview of the Learning-to-Forecast literature.2Hanaki et al (2019) are the first to term this phenomenon as the strategic environment effect.3 SeeMilgrom and Roberts (1990) for more examples.…”
mentioning
confidence: 99%